Salivary fluid secretion in the ixodid tick Rhipicephalus appendiculatus is inhibited by Thogoto virus infection. - Kaufman, W; Bowman, A; Nuttall, P (2001)
Adult Rhipicephatus appendiculatus ticks, infected with Thogoto (THO) virus or control, were fed on guinea pigs and removed at intervals throughout the feeding cycle. Salivary fluid secretion was measured by an in vitro technique. The salivary glands of infected, partially-fed ticks secreted fluid in vitro at about 75% the rate of controls, but the difference between infected and controls among engorged ticks was not statistically significant. Basal and DA-stimulated levels of cyclic AMP (cAMP) were determined in isolated glands and were significantly affected by THO virus infection. The differences in secretory rate among control and infected ticks could not be explained in terms of altered cAMP levels. Haemolymph volume was measured by a tracer-dilution technique using 3H-inulin. The mean haemolymph volume for both THO-infected and control groups was between 23-24% body weight throughout the feeding cycle, indicating that infection by this arbovirus did not influence salivary fluid secretion via altered haemolymph volume. The mechanism by which THO virus affects secretory activity of its tick vector remains unknown.